A simultaneous minimally invasive approach to treat a patient with coronary artery disease and metastatic lung cancer - Yuanhao Fu; Lufeng Zhang; Ling Ji; Chenyang Xu (Videosurgery and Other Miniinvasive Techniques)
Concurrent lung cancer and coronary artery disease requiring treatment with percutaneous coronary intervention or coronary artery bypass grafting is not rare. An individualized perioperative anticoagulation regimen and minimal surgical trauma will benefit the patient’s postoperative recovery. We successfully treated a 68-year-old female patient with a lesion in the left anterior descending artery and metastatic right lung carcinoma by simultaneous minimally invasive direct coronary artery bypass grafting via a small left thoracotomy and thoracoscopic wedge resection of the lung lesion. She recovered and was discharged on the eighth postoperative day. The patient showed no symptoms of myocardial ischemia postoperatively. Computed tomography scan did not indicate metastatic lesion of lung carcinoma at 1-year follow-up. In conclusion, minimally invasive direct coronary artery bypass grafting combined with thoracoscopic wedge resection is an effective minimally invasive treatment for concurrent lung cancer and coronary artery disease. This technique eliminates the risk of perioperative bleeding and provides satisfactory mid-term follow-up results.